Implementasi Algoritma Kalkulasi Interupsi pada Rancang Bangun Tachometer Digital - Maria, Putut Son; Susianti, Elva (Jurnal Teknik Elektro, 2018)
Tachometer is an important tool for measuring the rotational speed of electro-mechanical machines and other rotating objects. In a closed-loop system, it should have a mechanism by which sensory instruments must be able to produce and deliver feedback values that can be fetched by the controller. Most commercial tachometers do not have such data communication features, making it difficult to be employed in closed loop systems. This study aims to develop a tachometer which is programmed using calculation on interrupt-based algorithm and has data communication capabilities as well. The algorithm was designed over the minimum features of a microcontroller chip, namely a timer and interrupt. The proposed algorithm that was tested on the prototype results good performance for the typical electro-mechanical machines with a measurement error range between 0.1 and 1.2%. The equation for the calculation of rotation per minute (rpm) has also been revised to provide a more valid formula.